2015
DOI: 10.1002/2015wr016937
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms driving the seasonality of catchment scale nitrate export: Evidence for riparian ecohydrologic controls

Abstract: Considerable variability in the seasonal patterns of stream water nitrate (NO 2 3 ) has been observed in forested watersheds throughout the world. While many forested headwater catchments exhibit winter and early spring peaks in NO 2 3 concentrations, several watersheds have peak concentrations during the summer months. Pond Branch, a headwater catchment in Maryland monitored for over 10 years, exhibits recurrent and broad summer peaks in both NO export from June to September is particularly surprising, given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 56 publications
1
71
0
Order By: Relevance
“…Other recent studies have similarly reported riparian soils to be sources of N to streams in temperate [e.g. Duncan et al ., ] and Mediterranean [ Lupon et al ., ] catchments. While the underlying mechanisms in these studies differ from those highlighted here, together such observations suggest that this landscape pattern may be more common than is currently appreciated.…”
Section: Resultsmentioning
confidence: 99%
“…Other recent studies have similarly reported riparian soils to be sources of N to streams in temperate [e.g. Duncan et al ., ] and Mediterranean [ Lupon et al ., ] catchments. While the underlying mechanisms in these studies differ from those highlighted here, together such observations suggest that this landscape pattern may be more common than is currently appreciated.…”
Section: Resultsmentioning
confidence: 99%
“…Duncan et al . (), in turn, identified proximal controls, i.e., interactions between groundwater dynamics and nitrogen processes in the riparian zone, on NO 3 − concentrations during the summer months in their study watershed. However, other distal controls (e.g., senescence of vegetation) were considered as potential influences on NO 3 − concentrations and fluxes during different portions of the year.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, legacy-sediment-rich fill terraces have been shown to dampen N removal pathways in the long-buried relict soils which they overlie, while also acting as potential sources of nitrate (NO − 3 ) to waterways (Weitzman et al, 2014). Climate-driven export of N from watersheds is known to occur (Howarth et al, 2006;Lewis and Grimm, 2007;Kaushal et al, 2008aKaushal et al, , 2010Duncan et al, 2015), with N stored during "dry" years or seasons and flushed from watersheds during "wet" years or seasons. Such drying-rewetting cycles have been linked to regionwide pulses of high NO − 3 concentrations in tributaries of the Chesapeake Bay .…”
Section: Introductionmentioning
confidence: 99%